Aplikasi Kehadiran Karyawan Berbasis Android Menggunakan QR Code Scanning dan Location Based Service - Iskandar Yusuf; Henny Leidiyana (Journal of Informatic and Information Security, 2021)
Employee attendance is an administrative process that is carried out every day. Use of a manual system for events prone to damage or loss. Not to mention employees who forget attendance records, which will cause delays in the flow of employee attendance information. As a solution to the existing problems is by designing an application to make presence using Android-based QR Code Scanning and Location-Based Services (LBS). QR Code technology is very efficient because the code can be read in a very short time using a smartphone while the Location Based Service (LBS) is to prevent employees from making presence outside the area determined by the company. The design of this application produces a paperless system and prevents manipulation of attendance data because in this application it is implemented that one employee only asks for one device ID or smartphone IMEI